Reseña: Mazak, Catherine M. & Carroll, Kevin S. (Eds.). (2017). Translanguaging in higher education. Beyond monolingual ideologies. Bristol, United Kingdom: Multilingual Matters. - Paola Guerrero-Rodriguez (EuroAmerican Journal of Applied Linguistics and Languages, 2018)
This review focuses on the volume, Translanguaging in Higher Education, which offers a global perspective showing different translingual practices in a variety of geographic spaces through the eyes of different authors. The book goes beyond language teaching, substantially contributing to the emerging field of translanguaging as educational practice.